Pengaruh Kombinasi Konsentrasi AB Mix Dan Nutrisi Tanaman Organik terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus tricolor L.) Varietas Mira Sistem Hidroponik Wick - Restu Ramadhan, Dinda; Sondari, Nunung; Rakhmi Indriana, Kovertina (Fakultas Pertanian Universitas Winaya Mukti, 2025)
Red spinach is a leaf vegetable that has high economic value and contains protein, vitamin A, vitamin C and mineral salts that the body needs. Land conversion can have an impact on reducing agricultural land. One way to overcome this is to utilize existing land by planting hydroponically. The Wick hydroponic system is the simplest hydroponic system because it is easy to maintain. The research was carried out in Sukamandi Jaya Village, Ciasem District, Subang Regency with an altitude of between 100-300 meters above sea level from August to September 2024. This research was carried out with the aim of determining the effect of the combination of AB Mix levels and Nutriplan Organic Plant Nutrition from PT. Prima Agro Tech for the growth of red spinach plants using the Wick hydroponic system. RAK method (Randomized Block Design) with 5 treatments and 5 treatments, consisting of p1 = 100% AB Mix, p2 = 75% AB Mix + 25% Nutriplan, p3 = 50% AB Mix + 50% Nutriplan, p4 = 25% AB Mix + 75% Nutriplan, p5 = 100% Nutriplan. The experimental results showed that the type of nutrition had a significant effect on the parameters of plant height, number of leaves, root length, plant fresh weight, stem diameter and leaf area of red spinach (Amaranthus tricolor L.) Mira variety. The best treatment is p2 with 75% AB Mix + 25% Nutriplan, namely plant height 20.5 cm, number of leaves 25.6, root length 25.26 cm, fresh weight 13.97 cm, stem diameter 0.58 cm, and leaf area 49.93 cm2. Keywords: AB Mix, Nutriplan, Red spinach